Corynebacterium striatum Bacteremia during SARS-CoV2 Infection: Case Report, Literature Review, and Clinical Considerations - Andrea Marino; Edoardo Campanella; Stefano Stracquadanio; Manuela Ceccarelli; Aldo Zagami; Giuseppe Nunnari; Bruno Cacopardo (Infectious Disease Reports, 2022)
Bacterial infections, especially those in hospital settings, represent a major complication of COVID-19 patients, complicating management and worsening clinical outcomes. Corynebacterium striatum is a non-diphtheric actinobacterium that has been reported as being the causative agent of several different infections, affecting both immunocompetent and immunocompromised patients. Recently, C. striatum has been recognized as a nosocomial pathogen that is responsible for severe infection in critical patients, as well as in fragile and immunocompromised subjects. C. striatum has been described as the etiological agent of bacteremia, central line infections, and endocarditis. We report a case of a 91-year-old woman who was hospitalized due to SARS-CoV-2 infection, who developed C. striatum bacteremia and died despite antimicrobial therapy and clinical efforts. Furthermore, we discuss C. striatum diagnosis and treatment based on evidence from the scientific literature.